Georg Iggers, 1926–2017 - Wang, Q. Edward (Historein, 2018)
Georg Gerson Iggers, a world-renowned historiographer and cofounder of the International Commission for the History and Theory of Historiography, passed away in Buffalo, New York, on 26 November 2017. He was 90 years old.